2006
DOI: 10.1084/jem.20051659
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic recognition of flagellin by mouse macrophages restricts Legionella pneumophila infection

Abstract: To restrict infection by Legionella pneumophila, mouse macrophages require Naip5, a member of the nucleotide-binding oligomerization domain leucine-rich repeat family of pattern recognition receptors, which detect cytoplasmic microbial products. We report that mouse macrophages restricted L. pneumophila replication and initiated a proinflammatory program of cell death when flagellin contaminated their cytosol. Nuclear condensation, membrane permeability, and interleukin-1β secretion were triggered by type IV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
425
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(448 citation statements)
references
References 63 publications
15
425
2
6
Order By: Relevance
“…100,101 Similarly, other studies showed that NAIP5, a mouse parologue of NAIP, possibly in combination with IPAF, recognizes intracellular flagellin from Legionella pneumophila, in order to induce caspase-1 activation. 61,102,103 Moreover, early genetic studies in mice clearly identified NAIP5 as a L. pneumophila susceptibility locus, further delineating the importance of inflammatory caspases in the control of bacterial pathogens. 104 NALPs and the Biology of Reproduction: A Role for the Inflammatory Caspases?…”
Section: Intracellular Flagellin: Detection By the Nlr Proteins Naipmentioning
confidence: 99%
“…100,101 Similarly, other studies showed that NAIP5, a mouse parologue of NAIP, possibly in combination with IPAF, recognizes intracellular flagellin from Legionella pneumophila, in order to induce caspase-1 activation. 61,102,103 Moreover, early genetic studies in mice clearly identified NAIP5 as a L. pneumophila susceptibility locus, further delineating the importance of inflammatory caspases in the control of bacterial pathogens. 104 NALPs and the Biology of Reproduction: A Role for the Inflammatory Caspases?…”
Section: Intracellular Flagellin: Detection By the Nlr Proteins Naipmentioning
confidence: 99%
“…Several bacterial strains possess delivery systems responsible for the translocation of effector molecules into the host cytosol, which permit bacterial internalization and/or replication. 87,88 Disruption of the type four secretion system in Legionella pneumophila, 53,54,89 of the Listeria monocytogenes listeriolysin O, or of the type three secretion system in Salmonella typhimurium, 47,82,83 Shigella flexneri, 90 Yersinia pseudotuberculosis 55 and Pseudomonas aeruginosa 51 inhibits caspase-1 activation by these pathogens. Although initial reports had proposed that proteins of the type three secretion system, SipB in Salmonella 44 and IpaB in Shigella, 43 could directly bind and activate caspase-1, recent studies indicate a more indirect role for such bacterial delivery systems, presumably by allowing the inflammasome agonist to reach the cytosol.…”
Section: Modulation Of Caspase-1 Activitymentioning
confidence: 99%
“…The activating PAMPs, however, remained unknown. Genetic analyses of Legionella pneumophila and S. Typhimurium revealed that the delivery of flagellin into the cytosol was necessary for robust NLRC4-dependent caspase-1 activation and macrophage cell death [8][9][10][11]. Interestingly, high doses of S. Typhimurium induced flagellin-independent NLRC4 activation, suggesting that which was demonstrated for NLRC4 and also for NLRP1b, where cleavage was sufficient for activation with Bacillus anthracis lethal factor protease [28,29].…”
Section: Initial Recognition Of Pamps Is Mediated By Naipsmentioning
confidence: 94%